A study of prevalence of microalbuminuria in recently detected type 2 diabetes and its relation to hypertension, dyslipidaemia and obesity - Acharya, Shrikrishna V (Asian Journal of Medical Sciences, 2020)
Background: Microalbuminuria is one of the earliest markers of diabetic nephropathy, and if not recognized and treated early it may lead to diabetic nephropathy resulting in chronic renal failure. Aims and Objective: The aim of the current study was to find out the prevalence of microalbuminuria among newly detected Type 2 diabetic patients and also compare prevalence of microalbuminuria in patients with or without hypertension, dyslipidaemia and obesity. Materials and Methods: In this retrospective study, we analysed 90 patients with new onset type 2 diabetes mellitus. We divided the patients into two groups, group 1 with comorbidities like hypertension, dyslipidaemia and obesity (50 patients) and group 2 without comorbidities (40 patients). We analysed urinary microalbumin level in all patients and compared the prevalence of microalbuminuria between group 1 and group 2. Results: In our cohort of 90 patients, urinary microalbuminuria was found in 30 patients (33.3%). When we divided these nephropathy patients to group1 and group 2, we observed that group 1 with comorbidities had higher percentage of nephropathy patients i.e 24 out of 50(48%). Group 2 with 40 patients had only 6 patients with microalbiminuria ie 6 out of 40(15%). Incidence of microalbiminuria was higher in patients with hypertension, dyslipidaemia and obesity. Conclusions: We conclude that incidence of microalbiminuria is much more common in newly diagnosed type 2 diabetes. We also conclude that hypertension, obesity and hypercholesterolemia are risk factors for nephropathy and urinary microalbuminuria appears to be much more sensitive than serum creatinine as screening tool to detect diabetic nephropathy.